2007
DOI: 10.1088/0031-8949/76/5/003
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions of scattering states for the s-wave Schrödinger equation with the Manning–Rosen potential

Abstract: The exact solutions of s-wave scattering states for the Schrödinger equation with the Manning–Rosen potential are presented by the standard method. The normalized radial wavefunctions of scattering states on the ‘k/2πscale’ and the calculation formula of phase shifts are found. We also study the special case for α = 1 and find that this potential will reduce to the Hulthén potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…A useful analytical formula [68,78] that closely matches the numerical solution can be obtained by using the Hulthén potential V (r) = −α D m φ e −rm φ /(1 − e −rm φ ), which has similar behavior to the Yukawa potential for r → 0 and r → ∞. The solution is given by…”
Section: Constraining Sommerfeld Enhanced Modelsmentioning
confidence: 81%
“…A useful analytical formula [68,78] that closely matches the numerical solution can be obtained by using the Hulthén potential V (r) = −α D m φ e −rm φ /(1 − e −rm φ ), which has similar behavior to the Yukawa potential for r → 0 and r → ∞. The solution is given by…”
Section: Constraining Sommerfeld Enhanced Modelsmentioning
confidence: 81%
“…By comparing the above equation (45) with equation (18) and observing the relations of corresponding parameters, i.e., ↔ λ,δ ↔ δ andη = η, it is easy to find that equation (45) completely coincides with equation (18). It is well shown that the poles of S-matrix in the complex energy plane correspond to bound states for real poles and scattering states for complex poles in the lower half of the energy plane [28,29].…”
Section: Bound and Scattering States Of The Arbitrary −Wave Klein-gormentioning
confidence: 98%
“…The energy level E is determined by the energy equation (18), which is rather complicated transcendental equation. The correspondingly analytical wave functions can be expressed as…”
Section: Bound and Scattering States Of The Arbitrary −Wave Klein-gormentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the study of exponential-type potentials has attracted much attention from many authors (for example, cf, ). These physical potentials include the Woods-Saxon [7,8], Hulthén [9][10][11][12][13][14][15][16][17][18][19][20][21][22], modified hyperbolic-type [23], ManningRosen [24][25][26][27][28][29][30][31], the Eckart [32][33][34][35][36][37], the Pöschl-Teller [38] and the Rosen-Morse [39,40] potentials.…”
Section: Introductionmentioning
confidence: 99%